What Is the Place of Intermediate Care Unit in Patients with COVID-19? A Single Center Experience - Hale Bülbül; Gözde Derviş Hakim; Cengiz Ceylan; Murat Aysin; Şükran Köse (International Journal of Clinical Practice)
Introduction. COVID-19 pandemic has led to an increased rate of intensive care unit (ICU) stays. Intermediate care units (IMCUs) are a useful resource for the management of patients with severe COVID-19 that do not require ICU admission. In this research, we aimed to determine survival outcomes and parameters predicting mortality in patients who have been admitted to IMCU. Materials and Methods. Patients who were admitted to IMCU between April 2019 and January 2021 were analyzed retrospectively. Sociodemographics, clinical characteristics, and blood parameters on admission were compared between the patients who died in IMCU and the others. Blood parameters at discharge were compared between survived and deceased individuals. Survival analysis was performed via Kaplan–Meier analysis. Blood parameters predicting mortality were determined by univariate and multivariate Cox regression analysis. Results. A total of 140 patients were included within the scope of this study. The median age was 72.5 years, and 77 (55%) of them were male and 63 (45%) of them were female. A total of 37 (26.4%) patients deceased in IMCU, and 40 patients (28.5%) were transferred to ICU. Higher platelet count (HR 3.454; 95% CI 1.383–8.625; p=0.008), procalcitonin levels (HR 3.083; 95% CI 1.158–8.206; p=0.024), and lower oxygen saturation (HR 4.121; 95% CI 2.018–8.414; p<0.001) were associated with an increased risk of mortality in IMCU. At discharge from IMCU, higher procalcitonin levels (HR 2.809; 95% CI 1.216–6.487; p=0.016), lower platelet count (HR 2.269; 95% CI 1.012–5.085; p=0.047), and noninvasive mechanic ventilation requirement (HR 2.363; 95% CI 1.201–4.651; p=0.013) were associated with an increased risk of mortality. Median OS was found as 41 days. The overall survival rate was found 40% while the IMCU survival rate was 73.6%. Conclusions. IMCU seems to have a positive effect on survival in patients with severe COVID-19 infection. Close monitoring of these parameters and early intervention may improve survival rates and outcomes.